Peran Pendidikan Olahraga dalam Meningkatkan Kesehatan Fisik dan Mental Siswa: Sebuah Tinjauan Literatur - Indah Atifah Anwar, Nur (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2025)
This literature review explores the role of physical education in enhancing students’ physical and mental health, with a focus on its impact on physical fitness, psychological well-being, resilience, and social competence. By synthesizing findings from ten peer-reviewed international articles published between 2021 and 2025, the review highlights various contributions of school-based physical activity, including structured physical education lessons, the sport education model, high-intensity interval training (HIIT), and physical literacy programs. The analysis reveals that physical education offers significant benefits, such as reducing stress, anxiety, and depression, while improving self-esteem, social interaction, and overall well-being. Furthermore, effective program designs such as 15- to 45-minute sessions held at least three times per week consistently yield positive outcomes. Innovations in curriculum and the integration of physical literacy also enhance students' resilience and support the development of long-term healthy lifestyle habits. Nevertheless, challenges such as variation in intervention design, limited school resources, and unequal implementation remain obstacles. This review affirms that physical education plays a strategic role as both a preventive and promotive intervention in modern education and has the potential to serve as a foundational pillar for students’ lifelong physical and mental health